THE STRAFIFICATION OF CONSCIOUSNESS IN THE YOGACARA BUDDHISM PHILOSOPHY - Audrius Beinorius (Problemos)
The philosophical interpretation of the Buddhist concept of consciousness and stratification of its levels is analysed in the article with the reference to the Sanskrit sources of early Yogacara philosophy. A special attention is drawn to the treatises of Vasubandhu and by applying the phenomenological, comparative and semantic methods of research. The tradition of the Yogacara school emerged as a reaction to various metaphysical and psychological attitudes of Theravada Buddhism and to philosophical nihilism of Madhyamaka school. Vasubandhu considers that is very important to follow the radical empirical epistemology that was formulated by Buddha. In the very important his treatise Trimsika Vasubandhu strictly follows the early tradition of Abhidharma cannon and precisely analises all elements of the process of perception, by avoiding metaphysical implications of Sarvastivada school. In his analysis of the three phases of transformation (parinama) of consciousness he extends the traditional Buddhist structure of consciousness by changing the function of mental consciousness (mano-vijnana) and intelect (manas), and by introducing the new for Buddhist phenomenology of consciousness the concept of the store-consciousness(alaya-vijnana). Introducing of the concept of the store-consciousness helped for yogacaras to solve a lot of philosophical and psychological problems concerning the question of the nature of person. The issue of the reality of the external world is itself insignificant in Yogacara. The knowledge of the reality of the object is distorted by the personal perception and by the subjective mental conceptualisation. That is why his analysis of perception is directed against the existence of the metaphysical subject and the statement that it is possible to know anything purely objectively. What is real for him - not the ontological consciousness (vijnana), but purely epistemological representation-only (vijnapti-matrata).